Answer:
c) 0
Step-by-step explanation:
m= slope
m= (y2 -y1)/(x2-x1)
we have the points:
(12,6) and (-1,6)
x1= 12 y1= 6
x2= -1 y2= 6
so we have:
m= (6-6)/( -1 -12)
m= 0/ -13
m= 0
<span>answer
A) (-5,-49),(-2,-22),(3,23)
</span>when x = - 5 ; y=9x-4 = 9(-5) -4 = -49
when x = - 2 ; y=9x-4 = 9(-2) -4 = -22
when x = 3 ; y=9x-4 = 9(3) -4 = 23
Answer:
-5,-11 because it satisfies both equations
Step-by-step explanation:
Plug -5 into both equations and you get -11
Step-by-step explanation:
26. x²+5x+25/4 = (x + 5/2)²
29. x²/4y²-2/3+4y²/9x² = (x/2y - 2y/3x)²
Answer:
X = 116
Step-by-step explanation:
Total heptagon angle = 900
124 + 120 + 122 + 136 + 144 + 138 = 784
900 - 784 = 116